ChemInform Abstract: First Stable Nitrate‐Encapsulated Sandwich Type Polyoxometalate: Synthesis, Structural Characterization, and Catalytic Performance. Issue 23 (10th June 2014) - Farsani, Mostafa Riahi; Yadollahi, Bahram; Rudbari, Hadi Amiri; Amini, Akbar; Caradoc‐Davis, Tom; Price, Jason R.
Abstract Na4K5 [K3Cu3(NO3) (PW9O34)2] is synthesized from an aqueous solution of Na2WO4, Na2HPO4, Cu(NO3)2, and HCl (pH 7.5, 90 °C, 1 h followed by addition of KCl; 79% yield).